Nurse-Mediated Telehealth Follow-Up for Adults with COPD After Hospital Discharge: A Systematic Review of Hospital-to-Home Care Roles and Utilization Outcomes - Lianfeng Wang; Junlin Chen; Othman Talib (Home Health Care Management & Practice, 2026)
Objective: To synthesize evidence on nurse-mediated telehealth follow-up for adults with chronic obstructive pulmonary disease (COPD) after hospital discharge, focusing on nursing roles and acute care utilization outcomes. Methods: This systematic review followed PRISMA 2020 guidance. PubMed, Web of Science, CINAHL, and Embase were searched from inception to January 31, 2026. Randomized controlled trials and controlled nonrandomized intervention studies were included when adults with COPD received postdischarge telehealth follow-up, and nurses had a defined role in assessment, monitoring, education, triage, escalation, or care coordination. Risk of bias was assessed using RoB 2 or ROBINS-I. Narrative synthesis was primary, with exploratory random-effects pooling of comparable binary outcomes. Results: Ten studies from 7 countries were included: 9 randomized trials and 1 controlled nonrandomized before-and-after study. Interventions included telephone or video follow-up, home telemonitoring, electronic symptom diaries, mobile monitoring, and combined home visits with telephone support. Nurses contributed to symptom review, education, monitoring, triage, escalation, and care coordination, although nursing autonomy and response pathways were often poorly described. Two trials provided extractable binary hospital-related outcomes at approximately 6 months. The pooled estimate was favorable but imprecise (risk ratio, 0.56; 95% CI, 0.25-1.25; I 2 = 78%). Conclusions: Nurse-mediated telehealth may support COPD hospital-to-home transitions, but heterogeneous interventions, inconsistent outcomes, and incomplete reporting limit certainty. Future studies should clearly define nursing responsibilities, monitoring schedules, escalation thresholds, and standardized utilization outcomes.